2020
DOI: 10.3390/polym12020326
|View full text |Cite
|
Sign up to set email alerts
|

Matt Polyurethane Coating: Correlation of Surface Roughness on Measurement Length and Gloss

Abstract: Matt polyurethane coating was successfully prepared through the synergistic effect of castor oil and phenolic epoxy resin into polyurethane backbone. The formation mechanism may be ascribed to the modulus mismatch between the partially modified epoxy polyurethane and partially unmodified polyurethane. Scanning electron microscopy (SEM) was used to observe the micro-rough surface morphologies. Atomic force microscopy (AFM) and three-dimensional (3D) surface profilometer were applied to calculate a series of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Similar higher S a values were reported for silicate coatings on concrete and for inorganic dental porcelain [35,36]. Surface roughness of organic film-forming coatings can be below 1 µm [33]. However, the human's perception of a rough surface depends on the distribution of peaks and valleys.…”
Section: Surface Morphology Of the Cured Coatingssupporting
confidence: 77%
See 1 more Smart Citation
“…Similar higher S a values were reported for silicate coatings on concrete and for inorganic dental porcelain [35,36]. Surface roughness of organic film-forming coatings can be below 1 µm [33]. However, the human's perception of a rough surface depends on the distribution of peaks and valleys.…”
Section: Surface Morphology Of the Cured Coatingssupporting
confidence: 77%
“…The increase of the magnification reduced the analyzed area and probably consequently the impact of surface defects such as brush drags. The length-scale dependence of surface roughness parameters measured by CLSM has been demonstrated in literature [33]. Among the parameters, arithmetic average roughness S a (or R a ) is commonly chosen to express to surface roughness of materials.…”
Section: Surface Morphology Of the Cured Coatingsmentioning
confidence: 99%
“…Four evaluation sizes were analyzed from 50 × 50 µm to 5000 × 5000 µm. In case of certain parameters (e.g., Sa, Sq) tendencies were demonstrated in the values but other parameter values showed deviations (e.g., Ssk, Sku) [31]. [27].…”
Section: Designation Of Minimum Evaluation Areasmentioning
confidence: 97%
“…A survey of several studies revealed that the evaluation area seems to vary in a random manner, i.e., no relationship can be observed between the evaluation area and the applied machining procedure. Studies with the focus of minimization of the evaluation area can hardly be found [31]. In Table A1, examples are collected to demonstrate this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…3 Currently, extinction techniques are divided into physical extinction and chemical extinction within the industry. 4 Physical extinction refers to the way to fabricate extinction coatings via adding matting agents into bulk resin, such as natural fillers, micro wax powders, inorganic powders, and organic resin fillers. 5 Among all, the nano gas-phase SiO 2 powder is the most commonly used matting agent in the market.…”
Section: Introductionmentioning
confidence: 99%